Managing unlicensed street hawker by local government: A conceptual paper / Mohd Nazir Sukaimi, Farah Adilla Ab Rahman and Ahmad Faiz Yaakob - Ab Rahman, Mohd Nazir Sukaimi, Farah Adilla; Yaakob, Ahmad Faiz (2021)
The street hawker is a global phenomenon found in almost any country (Bromley, 2000). Street hawkers are also famous in developing countries' cities and towns (Alimi, 2016). In Malaysia, hawkers that operate illegally are not referred to as illegal hawkers because their merchandise is not prohibited from being sold; instead, their business is referred to as unlicensed hawkers because it falls under the jurisdiction of the local government (Undang- Undang Kecil Penjaja MBSA, 2007). To characterize hawkers, many writers and scholars have used terms like street hawking, food vendors, informal marketplaces, and informal street sellers" (Alan, 2019; Kadoo, 2017; Winter, 2017; Sarasmita, 2019). Nonetheless, it has the same connotation for people who run a business without permission or a license from the authorities. Some assert that Singapore's unique hawker culture belongs to Singapore; however, it belongs to Malaysia, as the two countries have a shared past (Alan, 2019). Since independence, street selling has been typical for unemployed and unskilled Malay residents and foreigners (Alan, 2019). Street hawking is a sort of self-employment that requires very little cash to operate (Alan, 2019). Most street hawkers offer food to the poor by providing low-cost meals. Local producers, such as those selling fruits, vegetables, eggs, and poultry; peddled sundries, such as those selling brooms, towels, and daily necessities; and essential service providers, such as street barbers, locksmiths, and cobblers, make up the rest of the street hawking group (Alan, 2019). Hawkers' mobility is done in a traditional fashion, such as depending on distance, either walking or pedaling to reach clients, and how many are selling items to mobile by carts, bicycles, or tricycles with cooking equipment (Alan, 2019).